Recovery from refractory chronic fatigue syndrome with CBT and modafinil. Issue 3 (22nd March 2021) - Garg, Himanshu; Douglas, Maggie; Turkington, Gordon Douglas; Turkington, Douglas
Abstract : Many patients with chronic fatigue syndrome (CFS) fail to derive benefit from evidence-based treatments such as cognitive–behavioural therapy (CBT) and graded exercise therapy leading to permanent disability. To discover whether a repeat prescription of modafinil might potentiate the benefits of CBT leading to social recovery as defined by 2 or more point improvement in energy and muscular pain/concentration and return to work or full-time training. Three patients with treatment-resistant CFS (mean duration 17.66 years) treated with modafinil and CBT in a Liaison Psychiatry clinic were retrospectively reviewed. Progress was reviewed at baseline, 4–6 months and 10–24 months. Patients rated their fatigue, pain and concentration using 10-point Likert scales. 2/3 achieved clinically meaningful improvements in energy and pain/concentration and 3/3 achieved social recovery. Modafinil, when prescribed over the medium term, would appear to be a potentially useful potentiating agent when added to CBT.